2009
DOI: 10.1105/tpc.108.062968
|View full text |Cite
|
Sign up to set email alerts
|

A Pivotal Role of the Basic Leucine Zipper Transcription Factor bZIP53 in the Regulation ofArabidopsisSeed Maturation Gene Expression Based on Heterodimerization and Protein Complex Formation

Abstract: Transcription of Arabidopsis thaliana seed maturation (MAT) genes is controlled by members of several transcription factor families, such as basic leucine zippers (bZIPs), B3s, MYBs, and DOFs. In this work, we identify Arabidopsis bZIP53 as a novel transcriptional regulator of MAT genes. bZIP53 expression in developing seeds precedes and overlaps that of its target genes. Gain-and loss-of-function approaches indicate a correlation between the amount of bZIP53 protein and MAT gene expression. Specific in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
218
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(233 citation statements)
references
References 56 publications
9
218
0
6
Order By: Relevance
“…Furthermore, distinct differences in the function of bZIP1 and bZIP53 become obvious when these plants were studied under a normal day/night cycle. As confirmed by immunoblot analysis, high-level expression of bZIP1 did not lead to obvious phenotypic changes, whereas medium-level expression of bZIP53 resulted in significantly reduced plant growth (Alonso et al, 2009). These findings indicate pronounced differences in bZIP1 and bZIP53 function.…”
Section: Bzip1 and Bzip53 Show Overlapping But Distinct Functions Inmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, distinct differences in the function of bZIP1 and bZIP53 become obvious when these plants were studied under a normal day/night cycle. As confirmed by immunoblot analysis, high-level expression of bZIP1 did not lead to obvious phenotypic changes, whereas medium-level expression of bZIP53 resulted in significantly reduced plant growth (Alonso et al, 2009). These findings indicate pronounced differences in bZIP1 and bZIP53 function.…”
Section: Bzip1 and Bzip53 Show Overlapping But Distinct Functions Inmentioning
confidence: 81%
“…Whereas Pro35S:bZIP1 plants grew normally under standard day-night cycles, Pro35S:bZIP53 plants showed a dwarf growth phenotype that depended on the expression level of the transgene (Alonso et al, 2009). Prolonged cultivation of the bZIP overexpressing lines in the dark resulted in an obvious phenotype ( Figure 1C).…”
Section: Ectopic Expression Of Bzip1 and Bzip53 Results In Enhanced Dmentioning
confidence: 99%
“…As bZIP11 and -44 showed the strongest activation potential on the GH3.3 promoter in protoplasts, we focused on these TFs applying stably transformed gain-of-function plants. Because constitutive ectopic expression of bZIP11-related bZIPs strongly interferes with plant growth 44,45 , we expressed the bZIPs as HA-tagged versions using a b-estradiol (Est)-inducible expression system (XVE) 46 . Quantitative real-time PCR (qRT-PCR) analysis revealed that GH3.3 induction correlated with an early increase of the bZIP11 regulator, which becomes detectable by immunoblot after 2 h of Est treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, these data suggest that bZIPs are not only involved in recruiting the acetylation machinery during auxin-induced transcription. As GREs frequently act as quantitative cis-elements in a wide array of stimulus-induced gene expressions 36,44,54,55 , it is tempting to speculate that GREmediated recruitment of SAGA complexes has a broader impact on gene regulation. Interestingly, the recruitment properties of the bZIPs for specific adapter proteins differ.…”
Section: Xvebzip44mentioning
confidence: 99%
See 1 more Smart Citation